(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Hepcidinis a novel biomarker to check the bioavailability of iron among Chronic Kidney Disease (CKD) patients across the world. The study was conducted to evaluate the relationship of serum Hepcidin level with inflammatory markers in CKD patients of stages 3-5. Materials and methods: This cross-sectional observational study was carried out in the Department of Nephrology of Chittagong Medical College Hospital for a period of one year. Eighty-five conveniently selected CKD patients (Stage 3-5) of whom Haemoglobin (Hb) concentration, iron indices, serum creatinine, C-reactive Protein (CRP) and serum hepcidin were measured. Spearman’s rank correlation coefficient was estimated, and simple linear regression was conducted. Results: Most of the study participants were male, and over 40 years of age. Median serum creatinine was 6.0 (IQR: 3.8-9.9) mg/dl and eGFR was 9.0 (IQR: 6-14) ml/min/1.73m2. However, serum ferritin was higher among the high hepcidin group (490.5 ng/ml) in comparison to that of the low hepcidin group (218 ng/ml). Similar findings were found for CRP (7 vs. 17) mg/l. A significant positive association of hepcidinwas found with the serum ferritin and a negative association with TIBC and TSAT. Conclusions: Study results would help to prove the relevance of hepcidinmeasurement among CKD patients in Bangladesh. JCMCTA 2023 ; 34 (1) : 95-99